Hybrid Contract in Sharia Insurance Practices in Indonesia - Noor Kholifah Hidayati; Ro'fah Setyowati; Maulidia Mulyani (Jurnal Ilmiah Ekonomi Islam, 2021)
The hybrid contract is a combination of several contracts. It exists due to the increasingly complex demands of human needs in contemporary times. However, its validity according to the Shari'a is still in doubt caused by a hadith of the Prophet that forbids the practice of two (or more) contracts if they are carried out in one transaction. In Indonesia, the hybrid contract is practiced in various transactions, one of which is the practice of sharia insurance. This causes the validity of the practice of sharia insurance to be questioned again. So the purpose of this research is to answer the problem: What is meant by hybrid contract and insurance? How is the hybrid contract mechanism in sharia insurance in Indonesia? How is the hybrid contract law in sharia insurance in Indonesia according to the 5 limits of the Al-Imrani contract?. This study uses a qualitative method with a deductive-inductive model. This library research includes analytical descriptive. The results of this study indicate that hybrid contracts in sharia insurance in Indonesia do not violate the hybrid contract restrictions that are prohibited by sharia according to Al-Imrani. So that the practice is legal by Sharia and the fatwa of DSN-MUI.